2018
DOI: 10.1111/cns.13081
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral immune response after stroke—A double edge sword for blood‐brain barrier integrity

Abstract: Summary The blood‐brain barrier (BBB) is a highly regulated interface that separates the peripheral circulation and the brain. It plays a vital role in regulating the trafficking of solutes, fluid, and cells at the blood‐brain interface and maintaining the homeostasis of brain microenvironment for normal neuronal activity. Growing evidence has led to the realization that ischemic stroke elicits profound immune responses in the circulation and the activation of multiple subsets of immune cells, which in turn af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 218 publications
(241 reference statements)
1
59
1
Order By: Relevance
“…The role of PVMs in BBB permeability is complicated. It is possible that PVMs facilitate BBB integrity under physiological conditions, while participate in BBB disruption under diseased status . Some evidence is discussed under Section 2.1 in this regard.…”
Section: Pvm Alterations In Diseased Brainmentioning
confidence: 99%
“…The role of PVMs in BBB permeability is complicated. It is possible that PVMs facilitate BBB integrity under physiological conditions, while participate in BBB disruption under diseased status . Some evidence is discussed under Section 2.1 in this regard.…”
Section: Pvm Alterations In Diseased Brainmentioning
confidence: 99%
“…It has been suggested that RSG, a PPAR‐γ agonist, can drive microglial/macrophage polarization and phenotypic change, which is highly dynamic after ischemic injury . We next examined whether RSG treatment altered the function and phenotypic change of microglia/macrophage in the tPA‐treated stroke mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is emerging that the PPAR‐γ is constitutively expressed in microglia and activating PPAR‐γ in microglia may regulate the phenotypic change of microglia . PPAR‐γ activation could favor a reprogramming process of microglia toward a beneficial phenotype, with anti‐inflammatory and tissue‐repair properties . Interestingly, previous studies have shown that 1 day after ischemia, the microglia/macrophages adopt an anti‐inflammatory phenotype that progressively evolves toward a neurotoxic phenotype at day 7 poststroke .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this direct interaction is time‐dependent warrants further investigation. Manipulating CNS‐periphery crosstalk to impair proinflammatory N1 neutrophils and amplify the effect of N2 neutrophils may be a feasible treatment approach for stroke …”
Section: Microglia‐neighboring Cells Crosstalk and Interventions For mentioning
confidence: 99%